Electroclinical and Multimodality Neuroimaging Characteristics and Predictors of Post-Surgical Outcome in Focal Cortical Dysplasia Type IIIa - Zhang, Lingling; Zhou, Hailing; Zhang, Wei; Ling, Xueying; Zeng, Chunyuan; Tang, Yongjin; Gan, Jiefeng; Tan, Qinghua; Hu, Xiangshu; Li, Hainan; Cheng, Baijie; Xu, Hao; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Focal cortical dysplasia (FCD) type IIIa is an easily ignored cause of intractable temporal lobe epilepsy. This study aimed to analyze the clinical, electrophysiological and imaging characteristics in FCD type IIIa, and search for predictors associated with postoperative outcome in order to identify potential candidates for epilepsy surgery. We performed a retrospective review including sixty-six patients with FCD type IIIa who underwent resection for drug-resistant epilepsy. We evaluated the clinical, electrophysiological and neuroimaging features for potential association with seizure outcome. Univariate and multivariate analysis was conducted to explore their predictive role on the seizure outcome. We demonstrated that thirty-nine (59.1%) patients had seizure freedom outcome (Engel class Ia) with a median postsurgical follow-up lasting 29.5 months. By univariate analysis, duration of epilepsy (less than 12 years) (P = 0.044), absence of contralateral insular lobe hypometabolism on PET/MRI (PLog-rank = 0.025), and complete resection of epileptogenic area (PLog-rank = 0.004) were associated with seizure outcome. The incomplete resection of epileptogenic area (Hazard ratio = 2.977, 95% confidence interval 1.218-7.277, P = 0.017) was only independent predictor for seizure recurrence after surgery by multivariate analysis. The results of past history, semiology, electrophysiological and MRI were not associated with seizure outcome. Carefully included patients with FCD type IIIa through comprehensive evaluation of their clinical, electrophysiological and neuroimaging characteristics can be good candidates for resection. Several preoperative factors appear to be predictive on the postoperative outcome and may help in optimising the selection of ideal candidates to benefit from epilepsy surgery.